2013
DOI: 10.9790/0853-0910105
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Yogic Exercise on Selected Pulmonary Function Tests in Apparently Healthy Elderly Subjects

Abstract: A case control study was done to find out the effects of simple yogic exercise programs (asanas and pranayamas) on selected pulmonary function tests of forty elderly individuals of both sexes, between 50 and 70 years of age, with no active medical disorders. The study was conducted at a selected yoga centre in Siliguri town of Darjeeling district of West Bengal. Forced Vital Capacity (FVC), Forced Expiratory Volume in one second (FEV 1) and Peak Expiratory Flow Rate (PEFR) were measured, once initially and aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…These findings are similar to those from some previous studies conducted by Biswas, 2 Yadav and Das, 7 Bal, 9 and some other researchers. 11,13,[33][34][35][36]39,[40][41][42][43][44][45][46][47][48][49][50][51][52][53] They supposed that FVC might be increased due to the strengthening of respiratory muscles by regular practicing of breathing exercises. 2,42,44,45 the removal of secretions from the bronchial tree, which made room in alveoli for more air after the breathing exercise.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings are similar to those from some previous studies conducted by Biswas, 2 Yadav and Das, 7 Bal, 9 and some other researchers. 11,13,[33][34][35][36]39,[40][41][42][43][44][45][46][47][48][49][50][51][52][53] They supposed that FVC might be increased due to the strengthening of respiratory muscles by regular practicing of breathing exercises. 2,42,44,45 the removal of secretions from the bronchial tree, which made room in alveoli for more air after the breathing exercise.…”
Section: Discussionmentioning
confidence: 99%
“…7,36 A significant improvement was noted for forced vital capacity (FVC), forced expiratory volume in 1st sec (FEV 1 ), maximum expiratory pressure (MEP), maximum inspiratory pressure (MIP), peak expiratory flow rate (PEFR), expiratory reserve volume (ERV) among healthy young subjects and also on healthy medical students. 7,13,31,34 The increase in MEP and MIP in the yoga group indicates that yoga improves the strength of both expiratory and inspiratory muscles. 33 This study was conducted with the aim to assess the physiological effects of short-term ANB exercise on respiratory function in healthy adult individuals under stressful conditions.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…A study performed on a group of elderly persons indicated that a short-term yoga practice (suryanamaskar and pranayama) was beneficial and prevented development of primary respiratory problems by increasing the efficacy of respiratory muscles. [4] Joshi et al [5] studied the significant increase in forced vital capacity (FVC) and peak expiratory flow rate (PEFR) following 6 weeks of pranayama practice. Bijlani [6] also reported similar observations.…”
Section: Introductionmentioning
confidence: 99%
“…These exercises help to empty and fill the respiratory apparatus more completely and efficiently, leading to increased development of respiratory musculature and result in significant improvement in pulmonary parameters like forced vital capacity (FVC), forced expiratory volume in 1st second (FEV1) and peak expiratory flow rate (PEFR). 5,6 There has been intensive study from various parts of the World on yoga. But, there is paucity of data, especially in North-East India, relating the effect of yoga on BMI and pulmonary function test in patients with type 2 diabetes mellitus.…”
mentioning
confidence: 99%